Lignocellulose biohydrogen towards net zero emission: A review on recent developments. (November 2022) - Lay, Chyi–How; Dharmaraja, Jeyaprakash; Shobana, Sutha; Arvindnarayan, Sundaram; Krishna Priya, Retnam; Jeyakumar, Rajesh Banu; Saratale, Rijuta Ganesh; Park, Young-Kwon; Kumar, Vinod; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Recent lignocellulosic pretreatments have been documented. Radiation energy based pretreatment techniques were discussed. Role of nanotechnology in bio–H2 production has been highlighted. Challenges in the development of pretreatments and remedies are suggested. Abstract: This review mainly determines novel and advance physical, chemical, physico–chemical, microbiological and nanotechnology–based pretreatment techniques in lignocellulosic biomass pretreatment for bio–H2 production. Further, aim of this review is to gain the knowledge on the lignocellulosic biomass pretreatment and its priority on the efficacy of bio–H2 and positive findings. The influence of various pretreatment techniques on the structure of lignocellulosic biomass have presented with the pros and cons, especially about the cellulose digestibility and the interference by generation of inhibitory compounds in the bio–enzymatic technique as such compounds is toxic. The result implies that the stepwise pretreatment technique only can ensure eventually the lignocellulosic biomass materials fermentation to yield bio–H2. Though, the mentioned pretreatment steps are still a challenge to procure cost–effective large–scale conversion of lignocellulosic biomass into fermentable sugars along with low inhibitory concentration.